Ayat-ayat Quran Sebagai Mantra Pengobatan - Janhari, M. Nurwathani (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
The position of the Quran as a medium of treatment is inseparable from the meaning of Al-Isra’ verse 82. However, the phenomenon of reciting the Quran as a medium of treatment sometimes gives rise to atomistic readings of the Qur'an, because there is a discrepancy between the context and the munasabah of the verse and the practice of treatment through Al- Quran. However, the phenomenon of atomistic reading of the Qur'an cannot be judge as an aberration but rather inevitability. This view is inseparable from the thesis developed by William A. Graham that the meaning of the Qur'an is obtained through repeated reading of the Qur'an. Because, for ordinary people, the meaning of the Qur'an is obtained through what they hear, what they see, and what they feel about the Qur'an itself. Departing from this background, this study aims to examine the use of verses from the Koran as a healing mantra in Ampenan District using a phenomenological approach. The results of this study indicate that the use of verses of the Qur'an as a healing spell is inseparable from the role of community leaders who make these verses a medium of treatment. For community leaders, treatment with the Qur'an is not just a cure for disease, but more than that, it is medicine, mercy, education, happiness, and of course as a medium to get closer to Allah SWT. Through the role of these community leaders, this spread and became a hereditary tradition of using verses from the Qur'an as healing spells. The public even though lay people do not understand the meaning of the verse at all. However, they feel the impact of reading the verse in the form of the disease they suffer in terms of improvements. Thus, it can be interpreted that the atomistic reading of the Qur'an cannot be said to be an aberration, because sometimes, reading with that model has the most impact on both ordinary and educated people. Keywords : Health Treatment, Medical Spells, Qur'anic Verses.